KONDISI MOTIVASI BELAJAR SISWA SELAMA IMPLEMENTASI PEMBELAJARAN JARAK JAUH DI TK SABILULUNGAN KOTA BANDUNG - Ita Puspita; Revita Yanuarsari; Fadila Rahma Ghoer (Pusat Riset dan Inovasi Nasional, 2023)
This research analyzes the condition of students' learning motivation during the implementation of distance learning in Sabilulungan Mekar Rahayu Kindergarten, Bandung City. This research was studied because there were problems regarding distance learning being implemented. The research objectives are to examine the condition of students' learning motivation, the implementation of distance learning and the strategies of teachers and parents in implementing distance learning. The research approach uses a descriptive approach with qualitative methods. Research respondents are parents of students, data collection techniques using interviews, documentation and observation. The results showed that the condition of students' motivation tended to be less enthusiastic and felt bored, while the implementation of distance learning using whatsapp groups and learning activities had been designed and referred to the RPPH and RPPM, PAUD educators' strategies at home (parents) in conducting guidance in distance learning. namely using discussion strategies (question-and-answer) and exemplary while the strategy carried out by the teacher is to use a reward strategy given to children to foster learning motivation and carry out regular zoom.